Effectiveness of Surgical Interventions for Self-Sucking in Dairy Cattle: A Comparative Study - Mohamed W. El-Sherif; Mahmoud S. Saber; Mohamed A. Abd Elkawy; Mahmoud A. Hassan (SVU-International Journal of Veterinary Sciences, 2023)
Self-sucking behavior in cows, is a behavioral defect that leads to significant milk loss in dairy farming. This retrospective case series aims to present the surgical experience and long-term outcomes of 200 cows exhibiting self-sucking behavior. The objective of this study is to evaluate the outcomes of four surgical techniques used to treat self-sucking in cows, including wound healing, complications, recurrence, and feeding difficulties. The follow-up period extended up to 2 years postoperatively, with repeated visits by the same surgeon. The study included 200 cows of mixed and native breeds. Four surgical techniques were employed to address self-sucking behavior. The same surgeon monitored the outcomes over time, assessing factors such as wound healing, complications, recurrence rates, and feeding difficulties. Long-term analysis revealed that the more invasive techniques, such as lateral glossectomy and ventral partial glossectomy, demonstrated the highest success rates at 100% and 96% respectively. In contrast, the less invasive techniques, ventral lingual inverting sutures and intralingual sutures, had success rates of 58% and 50% respectively. This study provides valuable insights into the long-term outcomes of various surgical techniques for correcting self-sucking behavior in cattle. The results indicate that lateral partial full thickness glossectomy yielded favorable outcomes with no recurrence and minimal postoperative complications. The findings from this study offer important considerations for decision-making regarding the optimal surgical correction of self-sucking in cattle, assisting veterinarians and farmers in selecting the most effective approach.